To simplify this expression, we can apply the laws of exponents.
First, let's simplify (2t^–3)^3.
Using the power of a power rule, we multiply the exponents:
(2t^–3)^3 = 2^3 * (t^–3)^3 = 8 * t^–9
Now let's simplify (0.4r)^2.
Using the power of a product rule, we square both the coefficient and the variable:
(0.4r)^2 = 0.4^2 * r^2 = 0.16 * r^2
Now we can combine the simplified expressions:
(8 * t^–9) * (0.16 * r^2) = 8 * 0.16 * t^–9 * r^2 = 1.28 * t^–9 * r^2
Therefore, the simplified expression is 1.28 * t^–9 * r^2.
Simplify (2t^–3)^3(0.4r)^2
1 answer